Carroll family papers - Carroll, Charles, 1702-1782.; Carroll, Charles, 1737-1832.
Correspondence, deeds, bills, accounts, and account books of Charles Carroll of Annapolis, Md.; correspondence addressed chiefly to William Gibbons, overseer; legal papers, financial papers, and family portraits of Charles Carroll of Carrollton, Md.
In part, positive and negative photocopies and handwritten transcripts.
Family members include Charles Carroll (1702-1782), landowner, of Annapolis, Md., and his son, Charles Carroll, member of the Continental Congress, signer of the Declaration of Independence, and U.S. senator, of Carrollton, Md.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Gibbons, William, -- active 1767-1829 -- Correspondence; Carroll family; United States. -- Continental Congress; Maryland -- Politics and government; Maryland -- Social life and customs; Delegates, U.S. Continental Congress -- Maryland; Landowners; Senators, U.S. Congress -- Maryland